EVALUASI PEMBELAJARAN MATEMATIKA SEKOLAH DASAR BERBASIS ASESMEN AUTENTIK - Siti Amini; Rahayu Retnaningsih; Sukiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics learning in elementary schools is not only oriented toward mastery of concepts and computational skills, but also toward students’ ability to apply mathematical knowledge in everyday life. Therefore, an evaluation system is needed that can comprehensively describe students’ learning achievements. Authentic assessment is one assessment approach that is relevant to supporting meaningful learning evaluation. This study aims to evaluate the implementation of elementary school mathematics learning based on authentic assessment. The study employed an evaluative method with a descriptive qualitative approach. The research subjects consisted of teachers and elementary school students. Data were collected through observation, interviews, and documentation. The results indicate that authentic assessment is able to provide a more comprehensive picture of students’ cognitive, affective, and psychomotor abilities in mathematics learning. However, its implementation still faces obstacles, particularly limited time and teachers’ understanding in designing authentic assessment instruments. Therefore, it is necessary to improve teachers’ competencies and provide school policy support so that the implementation of authentic assessment in mathematics learning can be carried out optimally.